Development of a socioemotional wealth importance (SEWi) scale for family firm research. Issue 1 (March 2016) - Debicki, Bart J.; Kellermanns, Franz W.; Chrisman, James J.; Pearson, Allison W.; Spencer, Barbara A.
Abstract: The importance attached to socioemotional wealth is thought to distinguish family firms from non-family firms. Yet, measurement of socioemotional wealth is difficult owing to an absence of psychometrically sound measures. In this paper, we describe the development of the socioemotional wealth importance scale (SEWi)—an instrument allowing direct measurement of the importance of socioemotional wealth to family owners and managers of family firms. We explain the processes used to generate items, pre-test the developed scale and validate it. The final construct is composed of three distinct dimensions: Family Prominence; Family Continuity; and Family Enrichment. Contributions and future research directions are discussed.